Research on Furniture Design Integrating Ming-Style Furniture Modeling Elements and Image Sensor Data: Taking Suitable Old Furniture as an Example - Wei Chen (Journal of Sensors, 2022)
Ming-style furniture, adhering to the excellent traditional Chinese history and culture, is the pinnacle of traditional Chinese-style furniture, which vividly embodies the cultural essence of Chinese-style furniture. However, with the current popularity of smart home products, there are many obstacles for elderly users to use smart home products. Voice interaction is one of the main interaction methods of smart home products. The design strategy of voice user interface for aging smart home products is studied to improve the experience of elderly users in operating smart home products. Based on image sensing technology, combining Ming-style furniture modeling elements, and based on context theory research, this paper proposes four types of smart home contexts for elderly users, including user context, task context, time context, and environmental context, so as to propose a specific smart home product voice user interface design strategy. According to the user’s situational characteristics, a multichannel interaction design of voice user interface is proposed, an emotional and personalized voice user interface is constructed, and a design strategy of context memory assisting the dialogue process is constructed. According to the task, time, and environmental situation of elderly users, it proposes design strategies such as active interactive voice user interface design and provides continuous behavioral service experience. Conclusion. The research results provide a method and strategy reference for the design and development of the voice user interface of smart home products and provide a more natural and comfortable experience of using smart home products for elderly users.